(untitled) (Journal on studies and research of academic knowledge, 2011)
The microbiological quality of cheeses farmhouse produced, normally made with raw milk, is basically dependent on hygienic and sanitary conditions adopted in the production system, processing and commercialization these products. From January to May 2011 was analyzed 30 samples of cheese farmhouse produced were obtained at different commerce places in Encarnación city. The results obtained show clearly that for fecal and total coliforms and E. Coli 25 samples (83%) were according to FIL 73A 1985 and APHA 1992 standards. For Staphylococcus coagulase-positive 100% of the samples were found acceptable according to FIL 145 1990 standard and were not isolated pathogens such as Salmonella sp, Shigella sp. And Pseudomonas sp. We describe the susceptibility to ?-lactam of 25 isolates of E.coli, 5 (20%) of these patients presented resistance to cephalosporins of 1°, 2°. and 3° generation. We conclude that handmade cheeses presented high microbial load, showing a profile that affect resistance to beta lactam antibiotics.